Perawatan Indirect Pulp Capping pada Gigi Tetap Muda (Laporan Kasus) - Suzanty Ariany; Heriandi Sutadi (Faculty of Dentistry, Universitas Indonesia, 2015)
Treatment for young permanent teeth with deep carious lesion that on radiographic examination close to the pulp and without symptoms and sign of pulp degeneration are indirect pulp capping. The aim of this technique is to maintain pulp vitality. Material used for this treatment must be able to stimulate reparative dentin, such as calcium hydroxide, zinc oxide eugenol, glass ionomer cement and bonding agent. This paper reported indirect pulp capping on young permanent tooth with deep carious lesion. After 7 months of observation there was no symptom and on radiographic examination showed reparative dentin.